Deashing Batubara Dengan Metode Leaching Menggunakan NaOH Dan HCL Di PT Bukit Baiduri Energi, Kabupaten Kutai Kartanegara, Kalimantan Timur - Saskiyah Saskiyah; Harjuni Hasan; Henny Magdalena (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Coal is one of the energy sources that is the basis for meeting energy and electricity needs in various countries, including Indonesia. Coal obtained from mining contains impurities, which can occur during coalification or during the mining process. There are impurities elements found in coal such as sulfur, ash and various other minerals found in coal. The sampling location was carried out at the mining location at PT Bukit Baiduri Energi, Kutai Kartanegara Regency, East Kalimantan Province. The solutions used in the deashing process using the leaching method are NaOH and HCl.